Acceptance of internet-based hearing healthcare among adults who fail a hearing screening. - Rothpletz, Ann M.; Moore, Ashley N.; Preminger, Jill E. (International Journal of Audiology, 2016)
Objective: This study measured help-seeking readiness and acceptance of existing internet-based hearing healthcare (IHHC) websites among a group of older adults who failed a hearing screening (Phase 1). It also explored the effects of brief training on participants’ acceptance of IHHC (Phase 2).Study sample: Twenty-seven adults (age 55+) who failed a hearing screening participated.Design: During Phase 1 participants were administered the University of Rhode Island Change Assessment (URICA) and patient technology acceptance model (PTAM) Questionnaire. During Phase 2 participants were randomly assigned to a training or control group. Training group participants attended an instructional class on existing IHHC websites. The control group received no training. The PTAM questionnaire was re-administered to both groups 4–6 weeks following the initial assessment.Results: The majority of participants were either considering or preparing to do something about their hearing loss, and were generally accepting of IHHC websites (Phase 1). The participants who underwent brief IHHC training reported increases in hearing healthcare knowledge and slight improvements in computer self-efficacy (Phase 2).Conclusions: Older adults who fail hearing screenings may be good candidates for IHHC. The incorporation of a simple user-interface and short-term training may optimize the usability of future IHHC programs for this population.